2008
DOI: 10.1097/01.tp.0000297247.08627.ff
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of Pancreatic Islets With Iron Oxide Nanoparticles for In Vivo Detection With Magnetic Resonance

Abstract: In vitro labeling of pancreatic islets with iron nanoparticles enables their direct posttransplant visualization by magnetic resonance; however, there is still a discrepancy in the fate of iron nanoparticles. This study was performed to detail the labeling process, consequently to improve the labeling efficacy and to confirm safety for islet cells. The islets were visible on T2*-weighted magnetic resonance images as hypointense spots immediately after 1-hr cultivation. Although at this time already the suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 14 publications
6
48
0
Order By: Relevance
“…Several additional MRI studies have reported that MRI is useful for the detection and monitoring of transplanted islets labeled with SPIO agents and the impact of labeling PI with SPIO has been tested extensively [9][10][11][12]26,[31][32][33][34]. These studies have shown that islet viability, insulin secretion, apoptosis levels and the islet structure as observed by electron and light microscopy are not affected by SPIO labeling at the levels required for detection by MRI.…”
Section: Discussionmentioning
confidence: 92%
“…Several additional MRI studies have reported that MRI is useful for the detection and monitoring of transplanted islets labeled with SPIO agents and the impact of labeling PI with SPIO has been tested extensively [9][10][11][12]26,[31][32][33][34]. These studies have shown that islet viability, insulin secretion, apoptosis levels and the islet structure as observed by electron and light microscopy are not affected by SPIO labeling at the levels required for detection by MRI.…”
Section: Discussionmentioning
confidence: 92%
“…19 The mechanism of cellular uptake of SPIO in islets is known as fluid-phase endocytosis. 17,20,21 Because labeling with ferucarbotran preceded the PEGylation process in this study, it is reasonable to assume that surface modification with PEG did not affect the uptake process of SPIO. To determine if PEGylation could affect the translocation of SPIO from intracellular to extracellular space during the early post-transplant period, we collected histological data 1 wk after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Preliminary experiments demonstrated superior labeling efficacy when isolated islets were allowed to culture in labeling medium for 48 vs. 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…shortening contrast agents based on super-paramagnetic iron oxide (SPIO) nanoparticles [2,3,[5][6][7][8] are used. In our study, a commercially available SPIO contrast agent (Resovist®, Schering AG, Berlin, Germany) based on carbodextran-coated iron-oxide nanoparticles, widely studied experimentally and also approved for human use [8], was used.…”
Section: Introductionmentioning
confidence: 99%